Mobilization of two retroelements, ZAM and Idefix, in a novel unstable line of Drosophila melanogaster. - Desset, S.; Conte, C.; Dimitri, P.; Calco, V.; Dastugue, B.; Vaury, C. (Molecular Biology and Evolution, 1999)
We describe a novel transposition system in a line of Drosophila melanogaster called RevI in which two retroelements are mobilized. These elements are the retroelement ZAM, recently described in the literature, and a novel element designated Idefix. Like ZAM, Idefix displays the structural features of a vertebrate retrovirus. Its three open reading frames encode predicted products resembling the products of the gag, pol, and env genes of retroviruses. In situ hybridization and Southern analyses performed on the RevI genome revealed the presence of some 20 copies of ZAM and Idefix, whereas ZAM is absent and Idefix is present in only four copies on the chromosomal arms of the original parental line. From RevI, a series of mutations affecting eye coloration has been recovered. The genetic and molecular analyses of these mutations have shown that most of them affected the white locus through three rounds of mutational events. The first mutational event was previously shown to be caused by a ZAM insertion 3 kb upstream of the transcription start site of white. It confers a red-brick phenotype to the orange eye coloration of the parental line. The second event results from the insertion of an Idefix copy 1.7 kb upstream of the transcription start site of the white gene, which modifies the red-brick phenotype to orange. This second mutational event was recovered as a recurrent specific mutation in 11 independent individuals. The third event results from an additional Idefix located 1.7 kb upstream of white that is responsible for the full reversion of the orange phenotype to red-brick. The fact that such mutations due to recurrent appearances of both ZAM and Idefix at the white locus result in such a variety of phenotypes brings to light a new molecular system in which the interference of mobile elements with the correct expression of the host gene can be tested.